Vulnérabilité de la population à Sfax (Centre-Est tunisien) aux conjonctivites : la synergie entre ambiance automnale et contexte de vie sociale - Mounir Jarraya (Territoire en Mouvement)
Characterized by its high heat and humidity, the autumnal bioclimatic atmosphere influences the ocular health of individuals in Sfax. The analysis of the effect of the thermo-hygrometric potentials of this atmosphere on the morbidity linked to conjunctivitis recorded by the Basic Health sector shows meteopathological aspects, since the degradation of bioclimatic comfort is associated with an increase in morbidity. Several elements related to the context of social life and the personal practices of individuals are taken into account to boost the inter-human transmission of conjunctivitis and their massive spread within the population and therefore explain the peak of medical consultations observed in autumn.